Dynamic cyclic fatigue resistance of NiTi instruments in a double-curved stainless steel canal with variable distances of displacement - Pham, Van-Khoa (Frontiers in Materials, 2023)
The aim of the present study is to measure the number of cycles to breakage fracture (NCF) of different instruments using pecking motion in constant distance and different distance of movement under body temperature. The twenty files of each brand of the ProTaper Universal F2, ProTaper Next X2, and WaveOne Gold Primary (Dentsply Sirona, Maillefer, Ballaigues, Switzerland) were included in the study. Instruments of each brand were divided by two groups (ten files for each group) that experienced the constant distance or variable distances in a stainless-steel artificial double-curved canal in a platform that ensured the instrument rotated in a stable temperature with a minimum fluctuation of the environment. While running, the platform was controlled programmable to move at any desired distance of instrument’s displacement to simulate the clinical pecking motion at variable distances. Files were rotated using proprietary programs and times to fracture were recorded then transformed into the number of cycles rounds rotated to breakagefracture (NCF). Data were analyzed using the Minitab with proper tests. All fragments were observed under a scanning electronic microscope to capture and describe the characteristic of the fracture surface. The WaveOne Gold had the highest rotated roundsNCF, and the ProTaper Universal had the lowest valueNCF. The brands of the manufacturer, the modes of displacement of the experimental instrument have interactive effects. The fracture surface reveals no striation. New design, material, mode of rotation and different distances of movement have certain effects on cyclic fatigue resistance of the instrument.